Combination of Red Coconut Coir (Cocos nucifera L. var rubescens) and Linezolid on Methicillin-Resistant Staphylococcus aureus in vitro Growth - Trisnawati Trisnawati; Wiwin Retnowati; Danti Nur Indiastuti (Biomolecular and Health Science Journal, 2020)
Introduction: Methicillin-Resistant Staphylococcus aureus (MRSA) bacterial infections may cause poor manifestations and even increase patients’ morbidity and mortality. The use of antibiotics in the management of infections remains the main therapy. However, ever-increasing antibacterial resistance has prompted researchers to find the solution. This study aimed to determine the effect of a combination of red coconut coir (Cocos nucifera L. var rubescens) in various concentrations and linezolid 10 µ/ml on the growth of MRSA bacteria in vitro.Methods: The antibacterial activity test method was well-diffusion test. Bacteria was plated in mueller hinton agar for 24 hours at 37oC. The treatment groups were red coconut coir extract and its combination with linezolid 10 µg/ml.  The well-diffusion test results were statistically analyzed with the One-Way ANOVA and Tukey HSD post-hoc tests.Results: Mean inhibitory zone diameter formed in the C. nucifera L. var rubescens extract test in various concentrations was 12.5 ± 0.36 - 16.2 ± 0.79 mm, while its combination with 10 µg/ml linezolid produced mean inhibitory zone of 15.1 ± 1.31-18.4 ± 0.46 mm. There was a significant difference between groups (p<0.05).Conclusion: Increasing concentration of C. nucifera L. var rubescens extract was in line with the increase of mean diameter of the inhibitory zone. Extract and antibiotic combination tests showed higher mean diameter zones than the single test of materials. The combination of extract and linezolid has the potential to synergistically prevent antibacterial resistance.